The Effect of Perceived Threat Avoidability of COVID-19 on Coping Strategies and Psychic Anxiety Among Chinese College Students in the Early Stage of COVID-19 Pandemic - Wu, Jinnan; Zheng, Yelianghui; Xiong, Shankuo; Zhang, Wenpei; Guo, Shanshan (Frontiers in Psychiatry, 2022)
Background: The COVID-19 outbreak has seriously threatened the mental health of college students. However, little is known about whether and how perceived threat avoidability of COVID-19 influences psychic anxiety, particularly in a sample of college students in the early stage of the COVID-19 pandemic. Methods: This study investigates the effect of perceived threat avoidability of COVID-19 on psychic anxiety, and the mediations of both emotion-focused (wishful thinking) and problem-focused (protective behaviors) coping strategies. Structural equation modeling and Bootstrapping procedure were used to test our hypotheses with a cross-sectional dataset consisting of 2922 samples from ten universities in China in February 2020. Results: Perceived threat avoidability of COVID-19 is negatively related to psychic anxiety, and both COVID-19-specific wishful thinking and protective behaviors mediate this relationship. Also, COVID-19-specific wishful thinking is found to correlate with COVID-19-specific protective behaviors negatively. Conclusions: Perceived threat avoidability of COVID-19 contributes to psychic anxiety among college students. COVID-19-specific wishful thinking strategy plays a negative mediating role and increases the level of anxiety; COVID-19-specific protective behaviors strategy plays a positive mediating role and reduces the level of anxiety; meanwhile, wishful thinking also suppresses college students from adopting protective behaviors.